The shadow of totalitarianism : action, judgment, and evil in politics - Burdman, Javier 1983- (SUNY series, intersections philosophy and critical theory, 2022)
Introduction : totalitarianism and the problem of evil in politics -- Arendt's reassessment of responsibility -- Kant on the deceptiveness of evil -- Kant on the sublime and the judgment of action -- Lyotard on good and evil in postmodernity -- Conclusion: Extreme evil as a response to political uncertainty.